Microbial Assay of Nystatin in Buffalo Bull Semen - SIDHU, S S; PANGAWKAR, G R; CHOUDHARY, R K (The Indian Journal of Animal Reproduction, 2023)
Semen samples from five he~lthy breeding buffalo bulls were· collected at regular intervals.Nystatin at concentration of 5, 20, 30 & 40 μg/ml was added to the semen, extended in Tris and frozen. After thawing, the samples werecentrifuged (3000 rpm/10 mts) and the drug was estimated in the seminal plasma. Theestimation of Nystatin was done by using Saccharomyces cervisiae as test organism. Thezone of inhibition in the seed -layer was taken for calculating the amount of nystatin recoveredfrom the seminal plasma in comparison to reference concentration after incubating at 30°C for 48 hrs. The assay was done to assess the suitable dose of nystatin to be added for effectivecontrol of fungi without significantly affecting the quality of semen. It was found that 30 μg/ml of Nystatin is sufficient to prevent the growthof fungi in preserved semen.
Keywords: Microbial Assay of Nystatin; Buffalo